Frequency of visits to Tomioka town and related factors among evacuees more than a decade after the Fukushima Daiichi Nuclear Power Plant accident - Matsunaga, Hitomi; Xiao, Xu; Hande, Varsha; Orita, Makiko; Kashiwazaki, Yuya; Taira, Yasuyuki; Takamura, Noboru (Journal of radiation research, 2023)
This study aimed to clarify the frequency of visits (FOV) to Tomioka town, Japan, and related factors among evacuees more than a decade after the Fukushima Daiichi Nuclear Power Plant accident. A questionnaire survey was conducted on residents (age ≥ 18 years) who had residence cards in August 2021. Of the 2260 respondents, the FOV to Tomioka was as follows: 926 (41.0%) more than twice a year (Group 1 [G1]), 841 (37.2%) once a year (G2) and 493 (21.8%) no visits (G3). About 70% of the respondents who had decided not to return to Tomioka visited once a year or more. No significant differences in the FOV or radiation risk perception were found between groups. Multinomial logistic regression analysis using G3 as a reference revealed independent associations between living inside Fukushima in G1 (odds ratio [OR] = 5.4, 95% confidence interval [CI]: 4.1–7.3; P < 0.01) and G2 (OR = 2.3, 95% CI: 1.8–3.0, P < 0.01), undecided about returning in G1 (OR = 2.5, 95% CI: 1.9–3.3, P < 0.01), females in G1 (OR = 2.0, 95% CI: 1.6–2.6, P < 0.01) and motivation to learn more about tritiated water in G2 (OR = 1.8, 95% CI: 1.3–2.4, P < 0.01). Overall, 80% of the residents had visited Tomioka within a decade after the accident. These findings suggest the need to continue the effective dissemination of information about the effects of a nuclear accident and the subsequent decommissioning process to evacuees after evacuation orders have been lifted.